88.5k views
3 votes
99 POINTS

Solve the system using elimination. Show your work.
2x – 3y = 18
x + y = 14



Check my answer.

Solve the system using substitution.
x = y – 3
2x + 4y = 16
Substitute x for y-3 to get y:
2x + 4y = 16
2(y-3) + 4y = 16
2(y) 2(-3) +4y (distribute) = 2y -6 +4y
2y - 6 +4y (combine like terms) = 6y -6
6y -6 +6 = 16 +6 (get rid of -6)= 6y=22
6y/6=22/6 (get y)= y=3.6
Substitute y for 3.6 to get x:
x = y-3
x = 3.6 - 3 = 0.6
x = 0.6
Final:
(0.6, 3.6)

User Jlalovi
by
5.7k points

1 Answer

6 votes

2x-3y=18

x+y=14

Want to find y first. Eliminate x. Multiply by 2 for x+y=14

2(x+y)=2(14)=2x+2y=28

2x-3y=18

2x+2y=28

Minus next:

2x-2x-3y+-2y=18-28

-3y-2y=-10

-5y=-10

Divide by -5

-5y/-5=-10/5

y=2

Substitution method

2x-3y=18

2x-3(2)=18

2x-6=18

Move -6 to the other side. Sign changes from -6 to +6.

2x-6+6=18+6

2x=24

Divide by 2

2x/2=24/2

x=12

Answer: (12,2)

User Chrisbajorin
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.